Answer:
(III), (VI),(VII), (I), (IV)
Step-by-step explanation:
Solving the system of equations one by one by elimination method
(I) 2x+y=10
x-3y= -2 ( multiply by 2)
we have unique solution
x=4, y=2
(II) 2x+y=10 (multiply by -3)
-6x-3y= -2
No solution.
(III) x+2y=5 (multiply by 2)
2x+y=4
Unique solution
x=1, y=2
(IV) 5x+ y= 33
x=18-4y ---> x+4y=18 (multiply by 5)
Unique solution
x=6, y=3
(V) Y=13 -2x ----> 2x+y=13 ( multiply by 4)
8x + 4y =52
No solution
(VI) x+ 3y =5
6x-y=11 (multiply by 3)
Unique solution
x=2, y=1
(VII) Y=10 + x ----> -x+y=10 (multiply by 2)
2x + 3y =45
Unique solution
x=3 , y=13
Values of x in increasing order= (III), (VI),(VII), (I), (IV)